2016
DOI: 10.18632/oncotarget.7338
|View full text |Cite
|
Sign up to set email alerts
|

A novel small molecule STAT3 inhibitor, LY5, inhibits cell viability, colony formation, and migration of colon and liver cancer cells

Abstract: Signal Transducer and Activator of Transcription 3 (STAT3) is persistently activated in human liver and colon cancer cells and is required for cancer cell viability, survival and migration. Therefore, inhibition of STAT3 signaling may be a viable therapeutic approach for these two cancers. We recently designed a non-peptide small molecule STAT3 inhibitor, LY5, using in silico site-directed Fragment-based drug design (FBDD). The inhibitory effect on STAT3 phosphorylation, cell viability, migration and colony fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…A lot of novel small molecular inhibitors of STAT3 have been reported to suppress cancer cells and tumor growth, such as LLL12 [22], LY5 [23], XZH-5 [24] and so on. However, to date, the translation of anti-STAT3 therapies into clinical trials has been difficult [2526].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of novel small molecular inhibitors of STAT3 have been reported to suppress cancer cells and tumor growth, such as LLL12 [22], LY5 [23], XZH-5 [24] and so on. However, to date, the translation of anti-STAT3 therapies into clinical trials has been difficult [2526].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as an approved drug by FDA, the security and permeability of Raloxifene are superior as compared to other reported novel molecular inhibitors of IL-6/GP130/STAT3, such as MDL-A [15], LLL12 [23], LY5 [24], and XZH-5 [25]. Therefore, Raloxifene is more likely to apply to clinical trails.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of miR-146a expression in hematopoietic cells is similar to that of treatment with LPS (10). Expression of miR-146a was upregulated in the process of leukemia cell apoptosis induced by multiple drugs such as imatinib and all-trans retinoic acid, which may be related to the pro-apoptotic or anti-apoptotic activities of multiple transcription factors (11,12). …”
Section: Discussionmentioning
confidence: 99%
“…The STAT family of proteins is responsible for transducing signals from growth factor receptors on the cytoplasmic membrane into the nucleus in order to regulate gene expression (12). Experiments using mutant cell lines and knockout mice have shown that STAT1 plays a significant role in interferon (IFN)-γ and IFN-α/β mediated signaling.…”
Section: Discussionmentioning
confidence: 99%
“…al. [66] a non-peptide small molecule STAT3 inhibitor, LY5, using in silico site-directed Fragment-based drug design (FBDD) was constructed. The inhibitory effect on STAT3 phosphorylation, cell viability, migration and colony forming ability by LY5 were examined in human liver and colon cancer cells.…”
Section: Gene Therapymentioning
confidence: 99%